Evaluation of fluid flow over stepped spillways using the finite volume method as a novel approach - Vosoughifar, Hamid Reza (Strojniški vestnik, 2013)
This research deals with the development of a Computational Fluid Dynamics (CFD) code called V-Flow using MATLAB for the two-dimensional modelling of unsteady flow over stepped spillways. V-Flow can be coupled with GAMBIT software and different spillway geometries can be modelled using voronoi mesh elements. The governing equations of flow over stepped spillways were discretized using the Finite Volume Method (FVM). The Power-Law scheme, implicit time approximation, GaussSeidel method, and SIMPLE algorithm were used for the discretization procedure. The flow was considered to be a laminar fluid flow with no turbulence model. The V-Flow model was validated against velocity vectors, streamlines, static pressures, dynamic pressures, and total pressures over the spillway obtained from the FLUENT model application. The experimental model simulated using both V-Flow and FLUENT for validation according to Gonzalezs experiments. A comparison between the results obtained from the application of the different models showed good agreement according to the mass imbalance, which serves as both a useful indicator of the convergence of the fluid flow solution and as an accuracy criterion to compare the V-Flow and FLUENT results.
Keywords: discretization; diskretizacija; finite volume method; metoda končnih volumnov; mreža po Voronoiu; numerical modelling; numerično modeliranje; roller compacted concrete; stepped spillways; stopničasti prelivi; valjani cementni beton; voronoi mesh